Evaluation method of spatial distribution characteristics for asphalt mixture structure based on Sholl analysis - Tengjiang Yu; Ziqi Chen; Fushou Zhao; Xiangrui Ji; Haitao Zhang; Shengsheng Ma (Case Studies in Construction Materials)
To further evaluate the reliability and rationality of asphalt mixture structure, the spatial distribution characteristics of void structure, mortar structure and aggregate structure were analyzed by combining computed tomography (CT) and Sholl analysis. Firstly, the spatial structure images of asphalt mixture specimen can be obtained through CT scanning test, and the independent void structure, mortar structure and aggregate structure have been obtained by combining digital image processing technology. Secondly, Sholl analysis was used to analyze different asphalt mixture structures and summarize their spatial distribution characteristics. Finally, the mortar structure in asphalt mixture with different voidage was further analyzed, and the related index factors affecting its spatial distribution characteristics were discussed, and the corresponding evaluation index was proposed. The results show that the spatial distribution characteristics of intersections for mortar structure are relatively more obvious. Asphalt type has little influence on the spatial distribution characteristics of Sholl technical indexes for mortar structure, while the aggregate structure and void structure have greater influence on it. Additionally, Sholl technical indexes of mortar structure can be divided into the statistical characteristics of intersections number (recommended Sum of intersections), the characteristics of intersections fitting curve (recommended Kurtosis) and the structure ramification state (recommended Schoenen Ramification index). The results provide a new way to evaluate the spatial distribution of asphalt mixture structure, enrich the reliability evaluation method of asphalt mixture structure, and contribute to the development of asphalt mixture structure evaluation technology.